2010
DOI: 10.1590/s0103-90162010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses and production of 'Syrah' vines as a function of training systems

Abstract: Plant architecture and its interaction with agricultural practices and environmental constraints is determinant for grapevine canopy structure, which is related to carbon assimilation, bud fertility and fruit quality. In this context, this study evaluated the performance of field-grown 'Syrah' grapevines conducted by two management systems: Vertical Shoot Position (VSP) or a modified Geneva Double Curtain (GDC), in Pirapora, state of Minas Gerais, Brazil, during the winters of 2007 and 2008. The evaluations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
(12 reference statements)
1
9
0
3
Order By: Relevance
“…The first studies carried out in the state of Minas Gerais showed that the ecological conditions of the autumn-winter season, such as low rainfall and high thermal amplitude, are favorable for improving Syrah grape composition from grapevines grown under warm temperate and tropical (Favero et al, 2010) climates in the south and north of the state, respectively. However, double pruning management had not been validated either for high altitude, or for late maturing cultivars, such as Cabernet Sauvignon.…”
Section: Introductionmentioning
confidence: 99%
“…The first studies carried out in the state of Minas Gerais showed that the ecological conditions of the autumn-winter season, such as low rainfall and high thermal amplitude, are favorable for improving Syrah grape composition from grapevines grown under warm temperate and tropical (Favero et al, 2010) climates in the south and north of the state, respectively. However, double pruning management had not been validated either for high altitude, or for late maturing cultivars, such as Cabernet Sauvignon.…”
Section: Introductionmentioning
confidence: 99%
“…A videira apresenta uma grande diversidade de arquitetura de seu dossel vegetativo e das partes perenes, constituindo os diferentes sistemas de condução encontrados. Os sistemas de condução, além de influenciar na ecofisiologia da planta (FAVERO et al 2010, NISHIOKA & MIZUNAGA 2011, pode afetar a produtividade do vinhedo (HERNANDES et al 2013, PEDRO JUNIOR et al 2013), a qualidade da uva (MOTA et al 2011, PALLIOTTI 2012, as características sensoriais e fenólicas dos vinhos (SEGADE et al 2009, FRAGASSO et al 2012) e a epidemiologia de doenças (BEM et al 2016, BEM et al 2017.…”
unclassified
“…Lyre-trained vines showed higher yields in the average of the harvests of the second growing season of the year (Table 3), as a consequence of the higher cluster number, which is in agreement with several studies on other cultivars in split canopy systems (Reynolds;Vanden Heuvel, 2009). Favero et al (2010) also found higher yields on 'Syrah' grapevines conducted with split canopy of GDC type compared to espalier, with similar results in 'Cabernet Sauvignon' (Pedro Júnior et al, 2016) and 'Riesling' (Reynolds et al, 2004). The higher yield of V. vinifera in divided canopy training systems such as lyre and GDC can be attributed to a greater exposed leaf surface for the light interception, as well as the higher number of buds per unit length of cordon (Reynolds;Vanden Heuvel, 2009).…”
Section: Resultsmentioning
confidence: 56%